2015
DOI: 10.1002/jcph.513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ceralifimod (ONO‐4641) on lymphocytes and cardiac function: Randomized, double‐blind, placebo‐controlled trial with an open‐label fingolimod arm

Abstract: This randomized, double-blind, placebo-controlled, 6-arm, parallel-design study investigated cardiac and hematological pharmacodynamic effects of ceralifimod (ONO-4641), a selective sphingosine-1-phosphate (S1P) receptor modulator, over a broad dose range in direct comparison with the nonselective S1P modulator fingolimod. Healthy subjects were assigned to ceralifimod (0.01, 0.025, 0.05, or 0.10 mg), fingolimod (0.5 mg), or placebo once daily for 14 days (n = 24 per group). After 14 days of treatment, mean abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 20 publications
4
42
0
Order By: Relevance
“…In their publication, Krösser and colleagues [48] have investigated the PK of ceralifimod. They showed that at the highest dose tested (0.1 mg), which triggered a decrease in total lymphocyte count from baseline of 56 %, median t max of ceralifimod …”
Section: Pharmacokinetics Of Ceralifimodmentioning
confidence: 98%
See 4 more Smart Citations
“…In their publication, Krösser and colleagues [48] have investigated the PK of ceralifimod. They showed that at the highest dose tested (0.1 mg), which triggered a decrease in total lymphocyte count from baseline of 56 %, median t max of ceralifimod …”
Section: Pharmacokinetics Of Ceralifimodmentioning
confidence: 98%
“…This property is of particular relevance in case of (desired) pregnancy or opportunistic infections, e.g., progressive multifocal leukoencephalopathy (PML) [83]. In this respect, lymphopenia after discontinuation of S1P receptor modulators differs widely and the lymphocyte count reaches normal values (e.g., ≥80 % of baseline) between one week with ponesimod [37], ceralifimod [48], and siponimod [47], more than two weeks with ozanimod [84], and up to 3 months with fingolimod [80].…”
Section: Treatment Of Multiple Sclerosismentioning
confidence: 99%
See 3 more Smart Citations